Paranucleospora theridion (Microsporidia) infection dynamics in farmed Atlantic salmon Salmo salar put to sea in spring and autumn - Sveen, Silje; Øverland, Hanne; Karlsbakk, Egil; Nylund, Are (Diseases of Aquatic Organisms, 2012)
The microsporidian Paranucleospora theridion (syn. Desmozoon lepeophtheirii) is a parasite of Atlantic salmon Salmo salar and also a hyperparasite of the salmon louse Lepeophtheirus salmonis. The parasite develops 2 types of spores in salmon, cytoplasmic spores in phagocytes and intranuclear spores in epidermal cells. The former type of development is assumed to be propagative (autoinfection), while the epidermal spores transfer the parasite to lice. Development in lice is extensive, with the formation of xenoma-like hypertrophic cells filled with microsporidian spores. We show that salmon are infected in the absence of lice, likely through waterborne spores that initiate infections in the gills. During summer and autumn the parasite propagates in the kidney, as evidenced by peaking normalised expression of P. theridion rRNA. Lice become infected during autumn, and develop extensive infections during winter. Lice mortality in winter and spring is likely responsible for a reservoir of spores in the water. Salmon transferred to sea in November (low temperature) did not show involvement of the kidney in parasite propagation and lice on such fish did not become infected. Apparently, low temperatures inhibit normal P. theridion development in salmon. 2017-10-10